Distributed energy storage systems for power networks - See, Cheng Yun. (2010)
The cost to the environment and the concern over source security are the two main motivations toward exploring new ways to meet energy demand. It will be fruitful if electrical energy can be stored at times of low load demand when the unit cost of energy production is low and the impact to the environment is minimal. The stored energy can then be released at times of high demand. Also, the Sun energy that is available to us almost every day is a good source of energy that can be captured and stored for reliable and controlled usage to lighten the electrical load from the grid.